Differential association of polymorphisms in the TNFα region with psoriatic arthritis but not psoriasis. Issue 3 (1st March 2002) - Höhler, T; Grossmann, S; Stradmann-Bellinghausen, B; Kaluza, W; Reuss, E; de Vlam, K; Veys, E; Märker-Hermann, E
Abstract : Objective: To investigate the potential association of tumour necrosis factor α (TNFα) microsatellite and promoter alleles with psoriatic arthritis (PsA). Methods: DNA from 89 white patients with PsA, 65 patients with psoriasis, and 99 healthy white controls was investigated for two TNFα promoter (–238 and –308) and three microsatellite polymorphisms (TNFa, c, and d). Patients had previously been studied by serology for HLA class I antigens and by sequence-specific polymerase chain reaction for DRB1* alleles. In addition, TNFα production of Ficoll separated peripheral blood mononuclear cells (PBMC) into culture supernatants after stimulation with lipopolysaccharide, αCD3 antibodies, phytohaemagglutinin, and streptococcal superantigen C was determined. Results: A significant, HLA class I independent increase of the TNFa6c1d3 haplotype was found in the group with PsA but not among patients with psoriasis (32% v 8%, pc<0.008; relative risk (RR)=5.3). In addition, patients with PsA showed a marked decrease of the TNF308A promoter allele (6% v 18%; pc<0.008; RR=3.5) compared with healthy controls, which was independent of the increased frequency of the –238A polymorphism in this group. PBMC from patients with PsA secreted significantly less TNFα than cells from patients without arthritis. In particular, the TNFa6 microsatellite was associated with decreased TNFα production. Conclusion: These data indicate that allelic variations at the TNFα locus influence susceptibility to PsA. Decreased production of TNFα is at least in part genetically determined and might be related to the development of arthritis. However, the association of the TNF308G allele with the disease also points to other disease related haplotypes with still unknown susceptibility genes.